Stress Distribution Around Dental Implant; Influence of Various Crowns- Fixture Ratio - Fazel A; Gerami Panah F; Zaratti S (Tehran University of Medical Sciences, 2000)
Preservation of bone-implant interface is vital for maintaining of implant treatment. There are some cases in which crown to fixture ratio is increased due to loss of residual ridge. In this condition knowledge of stresses acting over alveolar bone is important in regard to prognosis of treatment. In this study three different crown to fixture ratios evaluated under lateral forces considering stresses generated in the alveolar bone around the implant."nThree different models of crown to implant ratios were designed in a single-tooth implant at anterior maxilla."nModel No. 1 with ratio of 1:1, model No. 2 (1.5:1) and model No. 3 (2:1) were designed. Then, the differences between stresses under two horizontal loads (70 and 100 Newton) were analyzed by three-dimensional finite element analysis. Principal normal stresses and Vonmises stress were measured in this study."nResults indicated that stress concentration were mainly at the crestal bone."nHighest stresses were obtained in third model (2:1 ratio), which was approximately twice as first model (1:1) ratio.